Psychotic disorders in adolescents: symptoms, treatments and recovery - Rajoo, Keeren S. (Perpustakaan Sultan Abdul Samad, Universiti Putra Malaysia, 2015)
Psychosis is a serious mental illness that causes individuals to experience a reduced quality of life, while in severe cases, they can be harmful to both themselves and to others around them. When psychotic conditions manifest in adolescents, it also impairs their development. Early treatment of psychosis can significantly offset the damaging effects of this mental disease, especially among younger people.Unfortunately, there is limited information regarding psychosis in adolescents. This has caused a lack of understanding regarding this cognitive disorder, causing psychotic conditions in adolescents to often be overlooked by their guardians. This paper serves as tool for better understanding of this mental illness. Besides listing out the symptoms for identifying this disease, the current treatments available are also observed. It was found that more development is needed in the prescription drugs for psychotic conditions for adolescents, as the only ones available currently were developed for adults. Furthermore, the recovery process for these adolescents was plagued by prevalent societal stigma. Hence, it is obvious that more public awareness regarding this mental illness is necessary. There was also a very interesting observation in adolescents recovering from psychosis, as they were found to view their mental conditions positively.